Growth and photosynthetic responses of Quercus coccifera to CO2 enrichment and grazing - Mancilla-Leytón, Juan Manuel; Cambrollé, Jesús (Instituto de Ecología, A.C., 2019)
In the last century, human activities are precipitously increasing atmospheric CO2 concentration. In this future scenario of change, the objective of this work was to study the response of Quercus coccifera the combined effect of grazing and atmospheric CO2 enrichment. To examine the effects of partial consumption on seedling growth, three levels of grazing (null, moderate and high) and two atmospheric CO2 concentrations (380 µmol mol-1 and 700 µmol mol-1) were simulated. The results showed that the degree of simulated grazing was the main factor that could restrict the growth of seedlings of Q. coccifera; in both CO2 environments, plants with moderate grazing showed a significantly higher development than intact and high grazing plants. This study is a first approach on the Mediterranean scrub tolerance to grazing and enrichment atmospheric CO2 concentrations, but future studies are required that should shed light on many of the natural stress situations (abiotic and biotic).